Diversity of mast cell subpopulations in the tumor microenvironment of colorectal cancer and their prognostic implications - Tianyu Qiao; Chao Ding; Songtao Yu; Wenyang Li; Yonghou Zhao; Guiyu Wang (Cancer Immunology, Immunotherapy)
Abstract Background Colorectal cancer (CRC) is one of the most common and deadly malignancies worldwide, with a particularly low 5-year survival rate in advanced patients. Immune cells in the tumor microenvironment, especially mast cells, play crucial roles in tumor initiation and progression. However, the dual role of mast cells in CRC remains poorly understood. Methods In this study, we used single-cell RNA sequencing (scRNA-seq), bulk RNA sequencing, and bioinformatics analyses to explore the heterogeneity of mast cell subpopulations in the CRC tumor microenvironment and their relationship with prognosis. We analyzed gene expression signatures associated with mast cell subpopulations derived from single-cell data of 40 CRC tumor samples and combined bulk RNA-seq data from HMU, GEO, and TCGA cohorts for prognostic prediction. Non-negative matrix factorization was used for clustering of mast cell subpopulations, followed by analysis of their specific gene markers, transcription factor activity, and biological pathways. Survival analysis and ROC curves were performed to assess their prognostic significance. Results Mast cells in the CRC tumor microenvironment were classified into three distinct subpopulations, each with unique gene markers and functional pathways. Mast cell subpopulations 1 and 3 were highly associated with pro-tumor pathways, while mast cell subpopulation 2 primarily exhibited anti-tumor immune regulatory characteristics. High expression of mast cell subpopulations 1 and 3 was associated with poor survival prognosis, while high expression of subpopulation 2 was linked to a better survival outcome. Key marker genes such as DNAJB1, SEMA7A, and XCR1 were identified as potential prognostic factors, with high expression of DNAJB1 and SEMA7A being significantly associated with poor prognosis, while high expression of XCR1 was linked to a favorable prognosis. Conclusion This study reveals the functional heterogeneity of mast cell subpopulations in the CRC tumor microenvironment and their differential roles in tumor progression. Identification of mast cell subpopulation-specific marker genes provides new molecular targets for clinical diagnosis, prognostic prediction, and personalized immunotherapy in CRC.